Europeanisation and Globalisation of Higher Education in Central and Eastern Europe: 25 Years of Changes Revisited (1990-2015). Introduction to a Special Issue - Dobbins, Michael; Kwiek, Marek (My University, 2017)
For most countries it is safe to say that higher education (HE) is the segment of the education system which has changed the most over the past 50 years. Expansion, massification, greater female participation, privatization, the diversification of programmes, and more recently internationalization and globalization processes have radically transformed national HE systems. In Central and Eastern Europe (CEE), these processes of change have not only been much more abrupt and fastpaced than in the West, but have also run parallel to all-embracing political, economic and social transformations and, in many cases, nation-building. HE policy-makers in the region have been forced to tackle essentially all contemporary challenges confronting western HE systems within a much tighter timeframe and under much greater political and economic strain. HE reform has run parallel to the democratization of political institutions, the introduction of capitalism and, more recently, European integration. To complicate matters, CEE universities simultaneously struggled with the restoration of university self-governance and autonomy, academic freedoms, and the renewal of the academic profession. In numerous cases, HE was also at the apex of complicated national language and identity issues. Due its turbulent history and present, CEE higher education displays a striking diversity, which reflect nations’ diverging pre-communist and communist pathways as well as different contemporary sources of legitimacy. CEE is home to some of the most tradition-rich universities in Europe, including the Charles University of Prague (1348), Jagellionian University of Kraków (1364), University of Pécs (1367), and University of Vilnius (1578). Many others emerged during the era of nationalism and modernization in the eastern Slavic regions (e.g. the University of St. Petersburg, 1724; Lomonossov University, 1755). Nation building in the Balkans was also accompanied by the opening of numerous large universities in the 1800s (University of Belgrade, 1808; University of Iaşi, 1860; University of Bucharest, 1864; University of Sofia, 1888), many of which were inspired by Napoleonic notions of nationalism.
Keywords: Central Europe; higher education; Eastern Europe; postcommunist higher education; higher education reforms; expansion